POWER- AND RESOURCES-ECONOMY TECHNOLOGIES IN FOUNDRY - A. P. Melnikov (Литьë и металлургия, 2007)
The main activity directions in developments of NP RUP “Institute BelNIIlit”, which solve the complicated problems in the field of foundry and energy-saving are considered.